Pengembangan Lembar Kerja Peserta Didik untuk Meningkatkan Keterampilan Berpikir Kritis Siswa pada Materi Mollusca - Rojan Nurjannah; Epa Paujiah; Tri Wahyu Agustina (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to develop a Student Worksheet (LKPD) based on critical thinking skills on the topic of Mollusca and to evaluate the improvement in students' critical thinking skills following its use. This study employed the Research and Development (R&D) method using the 3D development model (Define, Design, Development), conducted at a senior high school in Bandung Regency, West Java, with 10th-grade students selected purposively as the research subjects; research instruments included validation forms completed by subject matter experts, pedagogical  experts,  and  biology  teachers,  as  well  as  pre-test  and  post-test questions to measure critical thinking skills; improvement data were analyzed using the normalized gain (n-gain) test. The results showed that the developed LKPD received the highest validation score from biology teachers at 92.8%, categorized as highly suitable, with an average pre-test score of 46 and post-test score of 71 yielding an n-gain of 0.49 in the moderate category, indicating that the use of the LKPD effectively improved students' critical thinking skills on the Mollusca topic. This study concludes that the critical thinking skills-based LKPD on the Mollusca topic developed using the 3D model has met the feasibility criteria and is proven to improve the critical thinking skills of 10th-grade students, making it suitable for use in biology instruction at the senior high school level.  Keywords: Biology Education, Critical Thinking Skills, Mollusca, Research and Development, Worksheets